Qualitative research in physical activity and the health professions - Pitney, William A. 1965-; Parker, Jenny 1964- (Human Kinetics, 2009)
Explains the principles of qualitative inquiry, making it easy for students and practitioners to understand how to design, conduct and evaluate qualitative research studies. This title provides a focused approach to qualitative research for students and professionals in physical activity and health care fields